La era del federalismo / Enrique Barón Crespo ; prólogo de, José Álvarez Junco ; epílogo dePablo Faura Enríquez y Domènec Ruiz Devesa - Álvarez Junco, JoséFaura Enríquez, PabloRuiz Devesa, Domènec; Barón, Enrique (1944-) (RBA actualidad. Política y sociedad)
Incluye referencias bibliográficas